A web-based system for automating the the assessment question setting and associated activities for Primary School mathematics : A - Ng, Wei Quan (2014)
Education system in Singapore has been acknowledged and ranked as one of the top in the world. Being a small country with limited natural resources, the government has placed huge emphasis on the importance of education and maintaining its high quality of education. As education in Singapore becomes more competitive, parents are increasingly concerned and see their child achieving top grades as a main priority. Schoolwork aside, parents and physical educators have been turning to assessment books to help the students further excel in their studies. As technology advances, online assessment tools being easily accessible have been in popular demand in the recent years. However, these existing tools in the market do not provide flexibility in expanding question range and accurate automated marking. The aim of this project is to develop an online assessment system for Primary Six level. Serving as an online platform for students, the system will have the ability to generate an unlimited number of questions randomly using different template types and random variables in the database. The system should also provide a higher accuracy in its automated marking function by using sequence to identify the marking model(s) for each type of question. This allows the marking of intermediate answers which is not available in current online assessment system in the market where only the final answer is being marked. With these improved functions, it will help physical educators and parents to better assess and monitor the student’s learning progress. The online assessment system was developed using Java, HTML, JSP and SQL with the use of Tomcat Server, MySQL Workbench and Eclipse as the platforms.